Performance and emission characteristics of an idi diesel engine fuelled biodiesel (Rubber Seed Oil and Palm Oil Mix) diesel blends - Adam, I.K. (EDP Sciences, 2014)
In this study crude rubber seed oil and palm oil were mixed at 50: 50 vol.feedstock's blending methods is motivated by cost reduction and properties enhancement. Biodiesel was produced and thermo physical properties are studied. Blends of B5, B10 and B20 of biodiesel to diesel were prepared. Engine performance (torque, brake specific fuel consumption (BSFC), brake thermal efficiency (BTE)) and emission (CO, NOx and exhaust gas temperature) were evaluated in a 4 cylinder, natural aspirated, indirect injection (IDI) diesel engine. The results indicated that at rated engine speed of 2500 rpm torque obtained were 87, 86, 85.3 and 85 Nm for neat diesel, B5, B10 and B20 respectively. Torque in all blends case yield between 0 to 5 lower than neat diesel. BTE were 27.58, 28.52, and 26.45 for B5, B10 and B20 compared to neat diesel 26.99. At lower blends ratio BSFC was found to be lower and increased proportional to the blends ratio. The CO emission reduced but the exhaust gas temperature and NOx increased as blends ratio increases. Â© 2014 Owned by the authors, published by EDP Sciences.